PERKEMBANGAN FASILITAS LAYANAN TABUNGAN BERBASIS TEKNOLOGI PADA BANK BUMN DI INDONESIA - Talita Cahaya Agusta (2022)
Savings is a banking service that is most popular among the general public, from urban to rural communities. According to the Banking Law No. 10 of 1998 article 1 (9), savings are deposits whose withdrawals can only be made according to certain agreed conditions, but cannot be withdrawn by check, bilyet giro, or other equivalent instrument. In the development of technology, banking launched a new technology called Electronic Banking or E-Banking. Electronic Banking is a banking product service facility that is influenced by technological developments and information that is offered directly to customers through electronic devices. E-Banking consists of SMS Banking, Mobile Banking, Internet Banking, electronic money, and Electronic Data Capture (EDC). This study uses a descriptive analysis research method, the data is obtained from the annual report of BUMN Bank (BNI, Mandiri, BRI) which will describe the increase and decrease in savings service facilities or E-Banking in the last three years (2019, 2020, 2021). The data that has been described will be compared, and this aims to find out which state-owned bank has the greatest increase in E-Banking services. The comparison is then analyzed to find out the causes of the increase and decrease in E-Banking services. The results of this study indicate that Electronic Banking is a technology-based savings service facility that is much favored by the public, in terms of cost and time which is very efficient. The Covid-19 pandemic that hit, forced people to carry out all activities from home, one of which was banking transaction activities. However, not all people understand how to access these savings services. Banks are asked to be more active in holding events related to technology-based savings service facilities or E-Banking so that people who do not know about these service features can immediately find out and use them in their daily lives to improve the use and performance of Digital Banking services.